The acuity of pediatric neuroscience nursing using the Inpatient Complexity Assessment and Monitoring to Ensure Optimal Outcomes (CAMEO©) tool. Issue 1 (27th August 2020) - Atkinson, Carole; Cerrato, Benjamin; Shiers, Deborah; Connor, Jean A.
Abstract: Purpose: The neuroscience nurse must possess advanced knowledge and skills to care for a wide range of unique congenital and acquired neurological diagnoses. For each of these clinical scenarios, the measurement of complexity and acuity of patient care is key to informing staffing models and patient assignments. The Inpatient Complexity Assessment and Monitoring to Ensure Optimal Outcomes (CAMEO © ) acuity tool measures patient acuity in terms of nursing cognitive workload complexity. We describe the implementation and evaluation of the Inpatient CAMEO © in a pediatric neuroscience unit in a large free‐standing children's hospital in the northeast United States. Design and Methods: Using a quality improvement approach, the Inpatient CAMEO © was implemented and evaluated over a 12‐month period by a neuroscience clinical lead and unit‐based ambassadors. Monthly data reports evaluating unit‐level completion and the level of acuity (I–V) were generated for unit leadership. Data were further stratified by type of admission to the neuroscience unit. Five categories of patients included neurology medical, epilepsy, neurosurgical, neurooncology, and other, which is defined as nonneurology patients, admitted to unit. Results: The monthly proportion of Inpatient CAMEO © s Classified as III–V ranged from 62.3% to 83.3% with a median of 78.2%. The type of neuroscience admissions varied in level of acuity. Patients identified as neurology (68.7%) and epilepsy (67.5%) had the lowest acuity, patients identified as neurosurgery (82.8%) and other (80.2%) had moderate acuity, and neurooncology (94.5%) had the highest acuity. Practice Implications: Using the Inpatient CAMEO ©, the acuity of neuroscience pediatric care was demonstrated to be increased and variable across disease categories. Neurooncology patients were identified as having the highest acuity as compared to other pediatric neuroscience admissions.